Penambahan Magnesium Oksida (MgO) Terhadap Sifat Sintesis Hidroksiapatit Berpori - Putra, Firmansyah Sophian (Jurnal Serambi Engineering, 2025)
Hydroxyapatite (HAp) is a bioceramic material widely used in the medical field, especially as a bone filler for bone tissue regeneration. However, pure HAp has low mechanical strength so that material modification is required. This study aims to examine the effect of the addition of Magnesium Oxide (MgO) and Polyvinyl Alcohol (PVA) on the morphological characteristics, functional groups, pore size, porosity, and Ca/P content of porous hydroxyapatite synthesized by the precipitation method. Variations in the weight percentage of MgO (14–18% wt) and the ratio of distilled water and Polyvinyl Alcohol (PVA) solution (20–60%) were used in the preparation of porous hydroxyapatite. Characterization includes spectrophotometric tests to analyze Ca/P content, morphological tests using SEM, functional group analysis using FTIR, and surface area analysis using BET. Based on the results of the test analysis that has been carried out, it is known that the porous hydroxyapatite sample with a variation of 1,8% MgO addition and 40% PVA ratio has a Ca/P value of 1,67 and has good characteristics for biomaterial applications with a granular morphological structure surface area of ​​7.3849 m2/g with an average pore size of 2.0274 nm, and is not toxic to health.